Efficient vacuum deposited p-i-n and n-i-p perovskite solar cells employing doped charge transport layers. Issue 11 (28th September 2016) - Momblona, Cristina; Gil-Escrig, Lidón; Bandiello, Enrico; Hutter, Eline M.; Sessolo, Michele; Lederer, Kay; Blochwitz-Nimoth, Jan; Bolink, Henk J.
Abstract : The use of small molecular weight intrinsic and doped transport layers allows to obtain fully vacuum deposited, efficient perovskite solar cells. Abstract : Methylammonium lead halide perovskites have emerged as high performance photovoltaic materials. Most of these solar cells are prepared via solution-processing and record efficiencies (>20%) have been obtained employing perovskites with mixed halides and organic cations on (mesoscopic) metal oxides. Here, we demonstrate fully vacuum deposited planar perovskite solar cells by depositing methylammonium lead iodide in between intrinsic and doped organic charge transport molecules. Two configurations, one inverted with respect to the other, p-i-n and n-i-p, are prepared and optimized leading to planar solar cells without hysteresis and very high efficiencies, 16.5% and 20%, respectively. It is the first time that a direct comparison between these two opposite device configurations has been reported. These fully vacuum deposited solar cells, employing doped organic charge transport layers, validate for the first time vacuum based processing as a real alternative for perovskite solar cell preparation.